Enhancing Image Classification Performance through Discrete Cosine Transformation on Augmented Facial Images using GANs - Şener, Abdullah; Ergen, Burhan (Ali KARCI, 2023)
The continuous advancements in technology are profoundly influencing various domains, including the realm of artificial intelligence. Within this field, the development and training of facial recognition systems have emerged as one of the most prominent research areas. Nowadays, facial recognition systems are rapidly replacing traditional security methods. In order to develop a good face recognition system, the training process must be provided with sufficient data. Recently, the number of open-source data that can help improve the accuracy of face recognition systems is limited. Generative Adversarial Networks (GANs) are a type of machine learning algorithm comprising two interconnected neural networks that engage in a competitive relationship. It is widely used in work domains such as image creation, image manipulation, super-resolution, text visualization, photorealistic images, speech production, and face aging. In the study, the lack of data for training face recognition systems was first solved with synthetic face images obtained with GANs. In the subsequent stage of the investigation, the aim was to enhance the image classification procedure through the application of the discrete cosine transform to the images. This approach aimed to fortify facial recognition systems against the presence of authentic-looking fabricated faces within virtual environments. In the study, it was found that the classification of faces could be improved by 30% compared to the normal classification model. The primary objective of this research endeavor is to make a significant contribution towards the development of highly accurate facial recognition systems.

Teknolojideki sürekli ilerlemeler, yapay zeka alanı da dahil olmak üzere çeşitli alanları derinden etkilemektedir. Bu alanda yüz tanıma sistemlerinin geliştirilmesi ve eğitimi öne çıkan araştırma alanlarından biri olarak ortaya çıkmıştır. Günümüzde yüz tanıma sistemleri hızla geleneksel güvenlik yöntemlerinin yerini alıyor. İyi bir yüz tanıma sisteminin geliştirilebilmesi için eğitim sürecine yeterli verinin sağlanması gerekmektedir. Son zamanlarda yüz tanıma sistemlerinin doğruluğunu artırmaya yardımcı olabilecek açık kaynaklı verilerin sayısı sınırlıdır. Üretken Çekişmeli Ağlar (GAN'lar), rekabetçi bir ilişki içinde olan birbirine bağlı iki sinir ağından oluşan bir tür makine öğrenme algoritmasıdır. Görüntü oluşturma, görüntü işleme, süper çözünürlük, metin görselleştirme, fotogerçekçi görüntüler, konuşma üretimi ve yüz yaşlandırma gibi çalışma alanlarında yaygın olarak kullanılmaktadır. Çalışmada yüz tanıma sistemlerinin eğitimi için veri eksikliği ilk olarak GAN'lar ile elde edilen sentetik yüz görüntüleri ile giderilmiştir. Araştırmanın sonraki aşamasında, görüntülere ayrık kosinüs dönüşümünün uygulanması yoluyla görüntü sınıflandırma prosedürünün geliştirilmesi amaçlandı. Bu yaklaşım, yüz tanıma sistemlerini sanal ortamlarda özgün görünen sahte yüzlerin varlığına karşı güçlendirmeyi amaçlıyordu. Çalışmada yüzlerin sınıflandırılmasının normal sınıflandırma modeline göre %30 oranında iyileştirilebildiği tespit edildi. Bu araştırma çabasının temel amacı, yüksek doğruluklu yüz tanıma sistemlerinin geliştirilmesine önemli bir katkı sağlamaktır.
GAN'lar Kullanılarak Artırılmış Yüz Görüntülerinde Ayrık Kosinüs Dönüşümü Yoluyla Görüntü Sınıflandırma Performansının Artırılması
Keywords: Image Processing; Görüntü İşleme; Deep Learning; Derin Öğrenme; Computer Software; Bilgisayar Yazılımı